PENINGKATAN PENGUASAAN KONSEP SIFAT-SIFAT CAHAYA PADA SISWA KELAS V SDN 1 RANDUAGUNG MELALUI MODEL PEMBELAJARAN INKUIRI - Afidhatul Atiyah; Arya Setya Nugroho (Universitas Muhammadiyah Gresik, 2020)
This research is motivated by the lack of enthusiasm of student in following IPA learning because the learning process is stil student centered whichcauses the mastery of the mastery of the concept of the material being studied, so that researchers apply the inquiry learning withthe aim of increasing mastey of concepts of light by using inquiry model of the students in grade V SDN 1Randuagung. This type of research is a classroom action research. The subjects of the study were 36 students ofgrade V SDN 1 Randuagung. Research design used is Arikunto research model. The data collection instrument used is a test sheet used to measure the mastery ofstudent concepts, student and teacher observation sheets used to measure the implementation of student and teacher activities in the application of inquiry. Data analysis of concept mastery and observation data analysis.Based on the results of research and discussion can be concluded that the instructional model of inquiry learning can improve the mastery of the concept of light students class V SDN 1 Randuagung. This can be seen from the everage value of concept mastery in cycle I that is 38,88% which experienced an increase in cycle II while still applying inquiry model that is with an average of 86, 11%.